2010
DOI: 10.1002/ccd.22652
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac echocardiography off piste? Closure of the left atrial appendage using ICE and local anesthesia

Abstract: Left atrial appendage (LAA) occlusion is increasingly accepted to reduce the risk of stroke in patients with atrial arrhythmia who are unsuitable for routine anticoagulation. It is generally performed under general anesthesia, guided by transoesophageal echocardiography with accurate imaging being essential for correct deployment of the device. We present a case where LAA occlusion was done under local anesthesia in a high-anesthetic risk patient, using novel placement of an intracardiac echo probe via a Mulli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Intracardiac echocardiography (ICE), commonly used for atrial septal defect or patent foramen ovale closure, offers guidance for structural interventional procedures in awake patients. LAA closure with ICE guidance has been reported in case reports or small case series with ICE performed from the right atrium (RA), 7,8 pulmonary artery, 9 or other right-sided locations. 10 More recently, Berti et al published a larger experience of LAA closure using right atrial ICE guidance, 11 reporting a technical success rate of 97.5% (117 of 121).…”
Section: R Esum Ementioning
confidence: 97%
“…Intracardiac echocardiography (ICE), commonly used for atrial septal defect or patent foramen ovale closure, offers guidance for structural interventional procedures in awake patients. LAA closure with ICE guidance has been reported in case reports or small case series with ICE performed from the right atrium (RA), 7,8 pulmonary artery, 9 or other right-sided locations. 10 More recently, Berti et al published a larger experience of LAA closure using right atrial ICE guidance, 11 reporting a technical success rate of 97.5% (117 of 121).…”
Section: R Esum Ementioning
confidence: 97%
“…17 A number of case series and studies have already demonstrated the ability of electronicprobe ICE to guide not only simple congenital [18][19][20] but also complex structural heart disease interventions, such as mitral valvuloplasty and clips, and left atrial appendage closure 21,22 and obviously in electrophysiology procedures. Moreover, mechanical-probe ICE was able to define accurately the anatomy in the case of tiny ostium primum, sinus defect, or the presence of anomalous pulmonary venous return, leading to a switch from catheter-based to surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The catheters are inserted from the ipsilateral or contralateral femoral vein via large venous sheaths and advanced from the inferior vena cava to the working position. The ICE probe can be positioned in the RA, the coronary sinus [56], the pulmonary artery [62] or the LA via a single-transseptal approach or after a second transseptal puncture [57]. Once the desired position is achieved, the probe can be set in that position with a lock mechanism.…”
Section: Alternative and Future Imaging Mo Dalities Intracardiac Echomentioning
confidence: 99%